Kinetics of various hydrocarbon groups formation in distillates obtained during the production of needle coke via the delayed coking of decantoil - Viacheslav A. Rudko; Ivan O. Derkunskii; Renat R. Gabdulkhakov; Rostislav R. Konoplin; Igor N. Pyagay (Egyptian Journal of Petroleum)
Carbon-graphite materials based on needle coke are fundamentally important for the development of related industries worldwide. This paper presents the study results of two types of decantoil coking distillates from the FCC plant, obtained in a laboratory simulation to produce petroleum needle coke. During coking, distillates were sampled by cut fractions at formation temperatures of 410–440, 440–470, 470–500, 500–505 °C. The hydrocarbon composition of the original decantoils and obtained cut fractions of the coking distillates were analysed by GC–MS. The selection of short-boiling-range products and analysis of their hydrocarbon composition allowed to estimate indirectly the stages of mesophase development and to determine the narrow temperature interval at which its most active development occurs. For the two types of decantoils this temperature interval is different (for D2 − 440–470 °C, for D1 − 470–500 °C). This phenomenon allows us to effectively determine the regime parameters of the delayed coking process for needle coke production. The formation kinetics (effective activation energy and pre-exponential factor) of different groups hydrocarbons, including paraffin-naphthenic, unsaturated, aromatic (mono-, bi- and polycyclic) for the first time was determined using the model-free Friedman isoconversion method. The obtained coefficients of determination are close to 0.9–1.